Plasmonic wave assessment via optomechatronics system for biosensor application - Abdullah, Muhammad Rosli; Harun, Noor Hasmiza; Ibrahim, Siti Noorjannah; Abdul Wahab, Azimah; Jamilan, Mohd Azerulazree (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Transduction biosensor (mass-based, optical and electrochemical) involves analysis, recognition and amplification in the acquired sample. In this work, the plasmonic-based biosensor was employed without using tags. It is crucial to determine angles of Brewster (Ɵb) and critical (Ɵc) for generating plasmonic resonance (Ɵr). The objective is to verify a cost-effective plasmonic biosensor through Fresnel simulation and experimentation of a developed optomechatronics system. The borosilicate glass, Au and Air layers were simulated with the Winspall 3.02 simulator. The optomechatronics system consists of: 1-optics (650 nm laser, slit, polarizer, photodiode), 2-mechanical (bipolar stepper motors, gears, stages) and 3-electronics (PIC18F4550, liquid crystal display (LCD) and drivers). Later, the software performs angular interrogation by reading the reflected beam from a rotating prism at 0.1125. Experimentation to simulation accuracy indicates that percentage differences for Ɵr and Ɵc are 1% and 0.2%, respectively. In conclusion, excellence verification was successfully achieved between experimentation and simulation. It proved that the low-cost optomechatronics system is capable and reliable to be deployed for the biosensor application.